POLITICAL CAPITAL, RATIONAL STRATEGY, AND PARTY DOMINANCE IN THE SELECTION OF THE VICE GOVERNOR OF THE RIAU ISLANDS - Euis Ammelia; Intan Idiani; Dian Mustika Intan (Politik Indonesia: Indonesian Political Science Review, 2024)
This article discusses the role of the Indonesian Democratic Party of Struggle (PDIP) in the election of Isdianto as Deputy Governor of the Riau Islands in 2017. Using a qualitative approach, the study analyzes political dynamics, party interactions, and institutional mechanisms within the Regional People's Representative Council (DPRD). The findings suggest that Isdianto's election was shaped by rational political calculations and transactional exchanges between actors, particularly amidst the instability of the governing coalition. PDIP leveraged its political networks and institutional influence to facilitate Isdianto's nomination and appointment. The study also identifies procedural irregularities, including the emergence of a single candidate and acclamation voting, which contravened existing regulations. These dynamics demonstrate symptoms of cartel politics and highlight weaknesses in Pasal 176 of UU No. 10/2016. The study concludes that rational choice theory better explains observed political behavior, emphasizing power, interests, and resource exchange as key determinants. This study contributes to debates on local democracy, party system institutionalization, and political recruitment in Indonesia.